2005
DOI: 10.1369/jhc.5a6705.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-specific Expression of β-Carotene 9', 10'-Monooxygenase in Human Tissues

Abstract: S U M M A R YThe symmetrically cleaving ␤ -carotene 15,15 Ј -monooxygenase (BCO1) catalyzes the first step in the conversion of provitamin A carotenoids to vitamin A in the mucosa of the small intestine. This enzyme is also expressed in epithelia in a variety of extraintestinal tissues. The newly discovered ␤ -carotene 9 Ј ,10 Ј -monooxygenase (BCO2) catalyzes asymmetric cleavage of carotenoids. To gain some insight into the physiological role of BCO2, we determined the expression pattern of BCO2 mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 32 publications
(38 reference statements)
7
100
0
1
Order By: Relevance
“…BCO2 is expressed in human normal prostate (21). To determine whether BCO2 is expressed in prostate cancer tissue, we first compared BCO2 protein lysates isolated from normal prostate tissues, benign prostatic hyperplasia (BPH), and prostate cancer tissues by Western blot analysis using an antibody specific for human anti-BCO2 antibody (Fig.…”
Section: Bco2 Expression Is Decreased In Human Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…BCO2 is expressed in human normal prostate (21). To determine whether BCO2 is expressed in prostate cancer tissue, we first compared BCO2 protein lysates isolated from normal prostate tissues, benign prostatic hyperplasia (BPH), and prostate cancer tissues by Western blot analysis using an antibody specific for human anti-BCO2 antibody (Fig.…”
Section: Bco2 Expression Is Decreased In Human Prostate Cancermentioning
confidence: 99%
“…Expression of the bco1 and bco2 genes overlaps in the human gastrointestinal tract, but bco2, additionally, is expressed in several tissues neither known to be sensitive to vitamin A deficiency nor to express bco1 (20,21). The discovery that BCO1-null mice cannot metabolize b-carotene to vitamin A despite intact bco2 expression (22) implicated BCO2 in biological processes other than vitamin A synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although beta-carotene cleavage activity was demonstrated in cell-free extracts derived from mammalian small intestine in the 1960s, purification of the enzyme proved surprisingly challenging [47][48][49][50]. It was not until the advent of molecular biological approaches and mass spectral sequencing that the beta-carotene cleavage enzyme was cloned first from Drosophila and chicken and later from humans [54][55][56][57][58]. It is a cytosolic enzyme primarily localized in the duodenal mucosa although it has been found in liver and in the eye.…”
Section: Carotenoid Metabolic Enzymesmentioning
confidence: 99%
“…It has been demonstrated that this enzyme can act on other carotenoids also; however, provitamin A activity might vary depending on the substrate. Cloning of mammalian proteins similar to the 15, 15′ β-carotene oxygenase has revealed the existence of RPE65 [54,56], a protein critical to the cis-trans isomerization of retinoids in the visual cycle, as well as an enzyme that catalyzes the asymmetric cleavage of beta-carotene at the 9′-10′ position [47][48][49]57].…”
Section: Carotenoid Metabolic Enzymesmentioning
confidence: 99%